2021
DOI: 10.1097/md.0000000000027112
|View full text |Cite
|
Sign up to set email alerts
|

Exploring potential mechanisms of Suhexiang Pill against COVID-19 based on network pharmacology and molecular docking

Abstract: Background: The traditional Chinese medicine prescription Suhexiang Pill (SHXP), a classic prescription for the treatment of plague, has been recommended in the 2019 Guideline for coronavirus disease 2019 (COVID-19) diagnosis and treatment of a severe type of COVID-19. However, the bioactive compounds and underlying mechanisms of SHXP for COVID-19 prevention and treatment have not yet been elucidated. This study investigates the mechanisms of SHXP in the treatment of COVID-19 based on network phar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Network pharmacological analysis of Suhexiang Pill (SHXP) found that 326 compounds were screened out, such as quercetin and so on, among which 6 central genes were closely related to the treatment of diseases, including IL6, IL10, EGFR, TNF, etc. Through GO enrichment analysis, its therapeutic effects are mediated by synergistic regulation of multiple biological signaling pathways, including Interleukin 17, Toll-like receptor, Nuclear factor kappa-b, Janus kinase/STAT3and hypoxia-inducible factor 1 signaling Pathways SHXP works to treat severe COVID-19 by moderating cytokine storms inhibiting viral growth and regulating the body’s immune system ( Li, et al, 2021a ). Studies have proved that TNF signaling pathway is an important pathway of the inflammatory response, and its related factor receptors can play a role by inducing apoptosis, while quercetin, an important component, also plays an anti-inflammatory role by regulating TNF signaling pathway ( Berntsen, et al, 2018 ; Nishikawa, et al, 2018 ; Pang, et al, 2018 ).…”
Section: The Application Of Network Pharmacology In the Study Of Tcm ...mentioning
confidence: 99%
“…Network pharmacological analysis of Suhexiang Pill (SHXP) found that 326 compounds were screened out, such as quercetin and so on, among which 6 central genes were closely related to the treatment of diseases, including IL6, IL10, EGFR, TNF, etc. Through GO enrichment analysis, its therapeutic effects are mediated by synergistic regulation of multiple biological signaling pathways, including Interleukin 17, Toll-like receptor, Nuclear factor kappa-b, Janus kinase/STAT3and hypoxia-inducible factor 1 signaling Pathways SHXP works to treat severe COVID-19 by moderating cytokine storms inhibiting viral growth and regulating the body’s immune system ( Li, et al, 2021a ). Studies have proved that TNF signaling pathway is an important pathway of the inflammatory response, and its related factor receptors can play a role by inducing apoptosis, while quercetin, an important component, also plays an anti-inflammatory role by regulating TNF signaling pathway ( Berntsen, et al, 2018 ; Nishikawa, et al, 2018 ; Pang, et al, 2018 ).…”
Section: The Application Of Network Pharmacology In the Study Of Tcm ...mentioning
confidence: 99%
“…In 1999, Shao Li firstly proposed the hypothesis that there is an interconnection between TCM and biomolecular networks. In September 2007, he constructed a research framework for TCM prescriptions based on biological networks [4]. Hopkins defined the concept of "network pharmacology" in October of the same year, the principle is to select specific nodes for multi-target drug design through network analysis of drug-target-disease, thereby improving the efficiency of drug development [5].…”
Section: Introductionmentioning
confidence: 99%